Exiting From Fragility in sub-Saharan Africa : The Role of Fiscal Policies and Fiscal Institutions - Delechat, Corinne; Fuli, Ejona; Glaser, Dafina; Ramirez, Gustavo (Washington, D.C. : International Monetary Fund, 2015)
This paper studies the role of fiscal policies and institutions in building resilience in sub-Saharan African countries during 1990-2013, with specific emphasis on a group of twenty-six countries that were deemed fragile in the 1990s. As the drivers of fragility and resilience are closely intertwined, we use GMM estimation as well as a probabilistic framework to address endogeneity and reverse causality. We find that fiscal institutions and fiscal space, namely the capacity to raise tax revenue and contain current spending, as well as lower military spending and, to some extent, higher social expenditure, are significantly and fairly robustly associated with building resilience. Similar conclusions arise from a study of the progression of a group of seven out of the twenty-six sub- Saharan African countries that managed to build resilience after years of civil unrest and/or violent conflict. These findings suggest relatively high returns to focusing on building sound fiscal institutions in fragile states. The international community can help this process through policy advice, technical assistance, and training on tax administration and budget reforms.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet